Pengaruh Akuntabilitas, Transparansi, PenerapanStandar Akuntansi Pemerintah Dan Penerapan SistemPengendalian Intern Terhadap Kualitas LaporanKeuangan Pemerintah Daerah(Studi Empiris Pada SKPD Kabupaten Sukoharjo) - Riyanti, Fina, Dr. Triyono, SE., M.Si (2017)
This research aims to know the effect of accountability, transparency, implementation of government accounting standards, the implementation of internal control system of quality Sukoharjo local government financial reports. The independent variables in this study are accountability, transparency, implementation of government accounting standards, the implementation of internal control system. This research included the quantitative research. The data is used primary data. Respondents in this research is the chairman, and the treasurer's accounting / budgeting SKPD Sukoharjo. The data analyzed by using multiple linier regression with SPSS software 17 version.. Methods of collecting data using a survey questionnaire distributed respondents. The results of this study indicate that (1) accountability affects the quality of financial reports of local government, (2) transparency does not affect the quality of the financial reports of local government, (3) the implementation of government accounting standards affect the quality of the financial reports of local government, and the implementation of internal control systems does not affect the quality of the financial reports of local government